Analysis Of The Constructs And Effects Of Integrating Social Work Embedded In Service-Oriented Community Governance - Guo, Wen Mei (2024)
This research aims to understand integrative social work practice in service-oriented community governance in china, by providing a detailed descriptive analysis of socio-demographic variables such as socio-cultural, socio-economic, and service demand. Three theories were used to provide the theoretical background for this research. First, social stratification theory provides important conceptual and analytical tools for analyzing and studying group differences. Inclusive governance theory is an important vector of good governance, while social systems theory ensures that systems function on their own in the integration process. In this qualitative study, a purposive sampling technique was used to select 41 participants from the jinfu community in china, including community councils, community residents, social workers, and volunteers. Primary data was collected from selected stakeholders through in-depth interviews. The data collected were analyzed using atlas.Ti8. Unstructured data collected through audio tapes, notes, and all other field data were analyzed using computer assisted qualitative data analysis software (caqdas) of atlas.Ti8.